Individual Autonomy as a Factor of Resilience of Young People - Pavićević, Olivera; Ilijić, Ljeposava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
The concept of resilience directs the approach to deficits and risks young people face when activating personal abilities and capabilities in solving problems. This concept implies that such personal capabilities appear under the influence of the milieu which recognises, cherishes and develops them. Resilience implies a risk and the response to it in the process of positive adaptation of adolescents and young people faced with new challenges in circumstances of uncertainty arisen by the loss of strict and well-known life guidelines and trajectories. The search for authenticity and autonomy must be a part of establishing moral coordinates based on a critical and responsible view of reality and human action. Independence in choosing implies assuming responsibility for it. Responsibility as the pivot of individual autonomy requires respecting social partners and selecting relations and resources which lead to a healthy and successful development based on the values which overcome the competitive individualism of a materialistic culture, as well as resilience with a low degree of individual autonomy relying too much on various types of vertical hierarchy.